Zastrupitve z gobami - Kirbiš, Simona (Medicinski razgledi, 2009)
There are about 200 different types of edible mushrooms and some 50 types of more or less poisonous mushrooms in Slovenia. Depending on the toxin and clinical presentation, mushroom poisoning is classified into various syndromes. This article presents a review of the mushroom groups causing individual poisoning syndromes and the pharmacodynamics and pharmacokinetics of the toxins, as well as the clinical presentation and treatment of the syndromes. The amatoxin, orelanine, muscarin, ibotenic, coprine, gyromitrin, gastrointestinal and psilocybin syndromes are described.
Keywords: Goba, zastrupitev; Mushroom Poisoning; diagnosis; Zdravljenje; Mikotoksini; therapy; Diagnostika; Amanitini; Muskarin; Mycotoxins; Psilocibin; Amanitins; Muscarine; gobe; Psilocybine; strupene gobe; toksini; toxin; zastrupitve